Ferromagnetic nanoclusters formed by Mn implantation in GaAs - Couto, O. D D; Brasil, M. J S P; Iikawa, F.; Giles, C.; Adriano, C.; Bortoleto, J. R R [UNESP]; Pudenzi, M. A A; Gutierrez, H. R.; Danilov, I. (AIP Publishing, 2005)
Ferromagnetic clusters were incorporated into GaAs samples by Mn implantation and subsequent annealing. The composition and structural properties of the Mn-based nanoclusters formed at the surface and buried into the GaAs sample were analyzed by x-ray and microscopic techniques. Our measurements indicate the presence of buried MnAs nanoclusters with a structural phase transition around 40 °C, in accord with the first-order magneto-structural phase transition of bulk MnAs. We discuss the structural behavior of these nanoclusters during their formation and phase transition, which is an important point for technological applications. © 2005 American Institute of Physics.
Keywords: Emission intensities; Ferromagnetic nanoclusters; Room temperature; Temperature dependence; Atomic force microscopy; Energy dispersive spectroscopy; Lattice constants; Manganese; Phase transitions; Secondary ion mass spectrometry; Semiconducting gallium arsenide; Thermal expansion; Transmission electron microscopy; X ray diffraction analysis; Ferromagnetic materials